Collaboration in Belgium : Léon Degrelle and the Rexist movement, 1940-1944 - Conway, Martin, 1960- (Yale University Press, 1993)
An exploration of the subject of collaboration during World War II in Belgium. The book demonstrates how the right-wing Catholic Rexist movement, led by Leon Degrelle, became one of the most important collaborationist movements in Nazi New Order Europe.